PEMULIHAN TRAUMA ANAK-ANAK KORBAN GEMPA DI KOTA PALU MELALUI MENDONGENG - Syamsuddin Syamsuddin (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2019)
This research is entitled ‘Trauma Recovery in Earthquake Victims in the City of Palu through Storytelling’. The problems in this study are (1) What strategies and techniques are used in storytelling in children affected by the earthquake in Palu, (2) What are the obstacles so far in storytelling activities in Palu City. The study was conducted in Palu City with the following considerations: (1) Palu City was the area most severely affected by the earthquake and many had casualties. (2) Many disaster victims' children need serious treatment in the process of recovering from trauma both those who have dropped out of school or those who have gone to school. The results showed: (1) Storytelling became one of the effective approach methods in recovering the trauma of children affected by the earthquake in Palu City. (2) Storytellers in Palu City are still lacking while there are quite a number of children who need psychological assistance. (3) The lack of institutions at the local level that focus on storytelling activities